2018
DOI: 10.1016/j.jdermsci.2018.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab treatment in moderate-to-severe atopic dermatitis: A systematic review and meta-analysis

Abstract: Our analysis provided evidence that dupilumab had an acceptable safety profile and resulted in clinically relevant improvements in signs and symptoms of AD. Dose regimens of 300 mg qw and q2 w seemed to have similar benefits. Further long-term trials are required for confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 25 publications
7
49
0
3
Order By: Relevance
“…Neurotrophins, especially NGF and its receptor, increase in nerve fibers of PN. 41 Interestingly, however, a recent find showed that none of the tested molecular markers including the neuron-distracting SEMA3A and neuron-attracting NGF altered in lesional and non-lesional skin in PN subjects. 40 Anti-NGF therapy can be used for the treatment of itch in NC/Nga AD mice, which could reduce the increased density of nerve fibers and the instances of scratching.…”
Section: Interleukin-4 and -13mentioning
confidence: 93%
See 1 more Smart Citation
“…Neurotrophins, especially NGF and its receptor, increase in nerve fibers of PN. 41 Interestingly, however, a recent find showed that none of the tested molecular markers including the neuron-distracting SEMA3A and neuron-attracting NGF altered in lesional and non-lesional skin in PN subjects. 40 Anti-NGF therapy can be used for the treatment of itch in NC/Nga AD mice, which could reduce the increased density of nerve fibers and the instances of scratching.…”
Section: Interleukin-4 and -13mentioning
confidence: 93%
“…In S ezary syndrome patients, NGF expression increases in keratinocytes, and nerve fiber density increases in the area of skin lesions. 41 Interestingly, however, a recent find showed that none of the tested molecular markers including the neuron-distracting SEMA3A and neuron-attracting NGF altered in lesional and non-lesional skin in PN subjects. 30 In addition, the NGF/TrkA/ TRPV1 pathway is considered as an important mechanism of psoriasis.…”
Section: Nerve Growth Factormentioning
confidence: 93%
“…[2][3][4] To date, knowledge about the use of biological antipsoriatic therapies in the management of difficult-to-treat body regions is fragmentary, lacking in agreement on the best therapeutic modalities and/or universally shared algorithm. [2][3][4][5][6][7][8][9][10] Here, we report the results of our perspective real-life study, aimed to evaluate the effect of biological drugs on difficult-to-treat psoriatic areas. Subjects were enrolled consecutively from patients attending the Psoriasis Care Center of the Outpatient Clinic of the Section of Dermatology, University of Naples Federico II, between March 2017 and January 2018.…”
Section: Real-life Effectiveness Of Biological Drugs On Psoriatic Difmentioning
confidence: 99%
“…No severe adverse effects have been reported. 8 The main limitation of our series is the lowest number of patients enrolled, but gives valuable preliminary information about the short-term efficacy and safety of dupilumab in realworld patients. Another limitation is having assessed SCORAD instead (or in addition to) EASI score, which may had allowed us to establish further and deeper comparisons to RCT.…”
mentioning
confidence: 99%
“…The ability to measure ‘consumption’ of topical treatment would also provide a useful outcome measure to assess the impact of emerging new drug‐based AD treatments, e.g. interleukin (IL)‐4/IL‐13, IL‐13 or Janus kinase 1 …”
mentioning
confidence: 99%